Effect of Different basal Media on Callus Growth and Morphology of Barringtonia Racemosa L Endosperms Explant - D A Kamaruzzaman, N; Saleh, A; Pardi, F; Ahmat, N; J Sidik, N (International Journal of Engineering and Technology, 2019)
Barringtonia racemosa L. has many medicinal properties especially the fruit and leaf parts. The fruits are used to relief pain and inflammation, the leaves were proved to control high blood pressure whereas the roots barks are effective to treat chicken pox. Due to its medicinal importance for human health, it is essential to conserve this plant. A comparative study of different types of media was performed to study its effect on callus growth of endosperm explant from B. racemosa. Types of basal media studied including Murashige and Skoog (MS), Lloyd and McCown Woody Plant (WPM) and Gamborg (B5). The endosperm explant of B. racemosa were cultured on different basal MS, WPM and B5 media supplemented with 1.0 mg/L 2,4-D and 1.5 mg/L kinetin. The observation of callus growth and morphological characteristics of callus were done on weekly basis within 4 weeks. After 4 weeks of incubation period, the maximum fresh weight (0.300 ± 0.027g) and dry weight (0.025 ± 0.003g) were recorded from the explants cultured on MS medium followed by WPM and B5 media supplemented with 1.0 mg/L 2,4-D and 1.5 mg/L kinetin. The textures of callus produced from MS were nodular in shape and creamy colour. In conclusion, all the media studied had successfully induced the callus growth of B. racemosa with the present of 1.0 mg/L 2,4-D and 1.5 mg/L kinetin.